2005
DOI: 10.1159/000089173
|View full text |Cite
|
Sign up to set email alerts
|

E-Cadherin Gene 3′-UTR C/T Polymorphism Is Associated with Prostate Cancer

Abstract: Introduction: E-cadherin (CDH-1) is a cell-cell adhesive molecule which maintains cell integrity and communication between the intracellular and extracellular world. CDH-1 may therefore be related to carcinogenesis. A polymorphism located at the 3′-UTR of the CDH-1 gene is associated with stone disease; however, its relationship to prostate cancer has not been reported. We aimed to study whether there is an association between the 3′-UTR polymorphism and prostate cancer. Materials and Methods: We collected 96 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
(21 reference statements)
0
11
1
Order By: Relevance
“…For example, 3 0 -UTR variations of both COX-2 and CYP2A6 are associated with an increased risk of lung cancer in Korean and Swedish populations, respectively (Park et al, 2006;Wang et al, 2006). Similarly, changes of the 3 0 -UTR of CDH-1 and Urokinase have been found to be associated with an increased risk of prostate cancer in Taiwanese and Indian populations (Mittal et al, 2005;Wu et al, 2005). Variations within the 3 0 -UTR sequences of the TYMS, DHFR, STK15, NPRA, CYP1A1, and BRCA1 genes have also been reported to be associated with an increased risk of specific cancers (Newman et al, 1998;Goto et al, 2001;Sarzani et al, 2003;DiCioccio et al, 2004;Zhang et al, 2005;Shin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, 3 0 -UTR variations of both COX-2 and CYP2A6 are associated with an increased risk of lung cancer in Korean and Swedish populations, respectively (Park et al, 2006;Wang et al, 2006). Similarly, changes of the 3 0 -UTR of CDH-1 and Urokinase have been found to be associated with an increased risk of prostate cancer in Taiwanese and Indian populations (Mittal et al, 2005;Wu et al, 2005). Variations within the 3 0 -UTR sequences of the TYMS, DHFR, STK15, NPRA, CYP1A1, and BRCA1 genes have also been reported to be associated with an increased risk of specific cancers (Newman et al, 1998;Goto et al, 2001;Sarzani et al, 2003;DiCioccio et al, 2004;Zhang et al, 2005;Shin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A missense variant in E-cadherin, S270A, was reported to be associated with prostate cancer risk in Finland [29] and 3 -untranslated region C/T polymorphism in Taiwan [30] . The most extensively studied variant, the -160C 1 A promoter polymorphisms, has been associated with increased prostate cancer risk in the Netherlands, Sweden and USA (carriers of AA, AC genotypes were found to be at higher cancer risk than carriers of CC genotype) [9,10,[31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…Although the function of the 3 0 -UTR C54 C/T polymorphism was unclear, studies have showed that this polymorphism was associated with cancer and other diseases (Tsai et al 2003, Wu et al 2005, Lin et al 2006. Wu et al found that the 'CC' homozygote indicates a relatively higher risk for developing prostate cancer than other genotypes (Lin et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These polymorphisms were associated with the development and progression of a certain cancer (Verhage et al 2002, Shin et al 2004a, Wu et al 2005. The relation between E-cadherin gene polymorphisms and the risk of developing endometriosis has not been reported.…”
Section: Introductionmentioning
confidence: 99%